Kampanye Slow Beauty Skincare di Kalangan Member Female Daily - Situmeang, Sherina Shadewi; Claretta, Dyva (Jurnal Pustaka Komunikasi, 2024)
The concept of slow beauty may be unfamiliar to some, but symbolically, certain skincare practices are interpreted as manifestations of these values. This study aims to explore the form of slow beauty campaigns in skincare among Female Daily members and identify the values of slow beauty being applied. The research employs netnography and a descriptive qualitative approach. Data was collected through online observation in FD Talk "Eco Friendly Product" and in-depth interviews. The results indicate that FD members have varied processes of identifying slow beauty values according to their own frameworks, especially in the context of using eco-friendly products. Out of the 13 aspects of Shel Pink's slow beauty concept, five aspects have been adopted by FD members based on their shared skincare practices. These include minimizing product consumption, using products until finished before replacing them, choosing beauty brands that support sustainability, avoiding fear of missing out on products, using eco-friendly products with multiple functions, and paying attention to the ethical production of inclusive local beauty products.